MODERN KARATE TEACHING METHODOLOGY (International Scientific Journal Alfraganus, 2024)
Are basically two approaches to learning the sport of karate, modern karate and traditionalkarate, there is no perfect approach to teaching modern karate because there are many methodsof teaching modern karate in the world, teaching modern karate is Important factors must betaken into account because, unlike traditional karate, modern karate changes. Due to the largenumber of learning methods, a study was conducted to analyze the different teaching methodsused in karate and to create a basis for defining these teaching methods. In this study, severalresearch methods were used to collect data. Competitions are held according to the rules approvedby the World Karate Federation (WKF). Among sports, karate exercises are distinguished bytheir complexity and unique nature. This requires conditionally paying attention to thedevelopment of all physical and mental characteristics of the athlete, mastering complexcoordination techniques with your legs and hands. Unpredictable tactical situations require theconstant need to make quick and effective tactical decisions. The existence of weight categoriesrequires a strategically thought-out physiological preparation for competitions, taking certaintactical measures necessary to reduce or reduce one’s weight in a short period of time. Also,winning means the need to create effective tactics of the dispute, using the anthropometriccharacteristics and anthropometric characteristics of the opponent.
Keywords: sport, practice, physical education, training, training process, modeling, karate, kata, kumite.